Performance of polydimethylsiloxane membrane contactor process for selective hydrogen sulfide removal from biogas - ÇALLI, BARIŞ (PERGAMON-ELSEVIER SCIENCE LTD, 2017)
H2S in biogas affects the co-generation performance adversely by corroding some critical components within the engine and it has to be removed in order to improve the biogas quality. This work presents the use of polydimethylsiloxane (PDMS) membrane contactor for selective removal of H2S from the biogas. Experiments were carried out to evaluate the effects of different pH of absorption liquid, biogas flowrate and temperature on the absorption performances. The results revealed that at the lowest loading rate (91 mg H2S/m2 h) more than 98% H2S and 59% CO2 absorption efficiencies were achieved. The CH4 content in the treated gas increased from 60 to 80% with nearly 5% CH4 loss. Increasing the pH (710) and loading rate (91355 mg H2S/m(2)h) enhanced the H2S absorption capacity, and the maximum H2S/CO2 and H2S/CH4 selectivity factors were 2.5 and 58, respectively. Temperature played a key role in the process and lower temperature was beneficial for intensifying H2S absorption performance. The highest H2S fluxes at pH 10 and 7 were 3.4 g/m(2) d and 1.8 g/m(2) d with overall mass transfer coefficients of 6.91 x 10(-6) and 4.99 x 10(-6) m/s, respectively. The results showed that moderately high H2S fluxes with low CH4 loss may be achieved by using a robust and cost-effective membrane based absorption process for desulfurization of biogas. A tubular PDMS membrane contactor was tested for the first time to remove H2S from biogas under slightly alkaline conditions and the suggested process could be a promising for real scale applications.
Keywords: Biogas cleaning; Membrane contactor; Hydrogen sulfide removal; Silicone membrane; AQUEOUS-SOLUTIONS; CARBON-DIOXIDE; MASS-TRANSFER; GAS; H2S; CO2; ABSORPTION; MIXTURE; SEPARATION; METHYLDIETHANOLAMINE